Challenges to regional economic integration in the Southern African Development Community bloc. (2nd July 2014) - Mapuva, Jephias
While different regional economic communities (RECs) have sought to grapple with economic and political challenges within their areas of jurisdiction, those of the SADC are unique in that they are inundated with many and varied such challenges. These challenges have negatively impacted on the region's propensity to provide economic benefits to the people of the region, unlike other groupings which have identified ways of dealing with their challenges. Among the most prevalent challenge to SADCs economic development has been the low gross domestic product (GDP) that has characterised the region's economic standing. Most importantly, the different challenges in the SADC have cumulatively impacted on the region's economic integration, although the conditions created by the region's members' small economies would have been ideal for regional economic integration and development.